Prospective, comparative clinical pilot study of cold atmospheric plasma device in the treatment of atopic dermatitis - Young Jae Kim (Nature Portfolio, 2021)
Abstract Cold atmospheric plasma generates free radicals through the ionization of air at room temperature. Its effect and safety profile as a treatment modality for atopic dermatitis lesions have not been evaluated prospectively enough. We aimed to investigate the effect and safety of cold atmospheric plasma in patients with atopic dermatitis with a prospective pilot study. Cold atmospheric plasma treatment or sham control treatment were applied respectively in randomly assigned and symmetric skin lesions. Three treatment sessions were performed at weeks 0, 1, and 2. Clinical severity indices were assessed at weeks 0, 1, 2, and 4 after treatment. Additionally, the microbial characteristics of the lesions before and after treatments were analyzed. We included 22 patients with mild to moderate atopic dermatitis presented with symmetric lesions. We found that cold atmospheric plasma can alleviate the clinical severity of atopic dermatitis. Modified atopic dermatitis antecubital severity and eczema area and severity index score were significantly decreased in the treated group. Furthermore, scoring of atopic dermatitis score and pruritic visual analog scales significantly improved. Microbiome analysis revealed significantly reduced proportion of Staphylococcus aureus in the treated group. Cold atmospheric plasma can significantly improve mild and moderate atopic dermatitis without safety issues.